2005
DOI: 10.1104/pp.104.058388
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Cell Death Induction by Phytophthora Elicitins Are Determined by Signal Components Downstream of MAP Kinase Kinase in Different Species of Nicotiana and Cultivars ofBrassica rapaandRaphanus sativus

Abstract: Elicitins are small, secreted proteins produced by species of the plant-pathogenic oomycete Phytophthora. They induce hypersensitive cell death in most Nicotiana species and in some cultivars of Brassica rapa and Raphanus sativus. In this study, two true-breeding Fast Cycling B. rapa lines were established that showed severe necrosis (line 7-R) or no visible response (line 18-NR) after treatment with elicitin. Unexpectedly, microscopic examination revealed localized cell death in line 18-NR plants, and express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 73 publications
2
24
0
Order By: Relevance
“…Treatment with elicitin induces typical defense responses, which is a form of programmed cell death, rapid generation of ROS, production of phytoalexins, expression of various defense-marker genes such as PR protein genes, and systemic acquired resistance to various pathogens in responsive plants (Takemoto et al, 2005). Consistent with this, a large first ROS burst at 0.5 h (Fig.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Treatment with elicitin induces typical defense responses, which is a form of programmed cell death, rapid generation of ROS, production of phytoalexins, expression of various defense-marker genes such as PR protein genes, and systemic acquired resistance to various pathogens in responsive plants (Takemoto et al, 2005). Consistent with this, a large first ROS burst at 0.5 h (Fig.…”
Section: Discussionsupporting
confidence: 66%
“…In compatible interactions with tobacco cell cultures, encystment of zoospores occurs within 2 h, followed by the penetration of cells and eventually prolific pathogen growth (Able et al, 1998). To monitor pathogen growth and the rate of cell death, we examined Ppn-inoculated plant leaves from wild-type and transgenic rbohD-as and rbohF-as mutants by photography after staining with lactophenol trypan blue (Takemoto et al, 2005). At 48 h after Ppn inoculation, cell death had significantly decreased in both transgenic plants, especially rbohD-as, in comparison with Ppn-inoculated wild-type plants (Fig.…”
Section: Impaired Ros Production Decreases Ethylene Biosynthesis and mentioning
confidence: 99%
“…However, cryptogein-induced ROS production was correlated with subsequent cell death in tobacco epidermis (Allan and Fluhr, 1997). Evidence also showed interactive signalling components in the regulation of tobacco cell death and defence response induced by INF1 (Kanneganti et al, 2006;Kamoun et al, 1998;Sasabe et al, 2000;Takemoto et al, 2005). INF1 induces H 2 O 2 generation via an NADPH oxidase and this contributes to plant resistance against pathogens (Asai et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In response to an elicitor, HCD develops as a microscopic hypersensitive response (micro-HR) with or without subsequent emergence of macroscopic HR (macro-HR). Micro-HR is induced more frequently than macro-HR Peng et al, 2004;Takemoto et al, 2005) and is required for macro-HR to be further induced (Peng et al, 2003). Both types of HCD occur as a result of intracellular transduction of reactive oxygen species (ROS) signals, such as hydrogen peroxide (H 2 O 2 ), O 2 · -, and hydroxyl radicals (Blokhina et al, 2003;Torres et al, 2006;Sagi and Fluhr, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Most MAMPs do not induce HR in plants; exceptions are the oomycete elicitins in tobacco (Takemoto et al, 2005) or fungal xylanase in tomato (Ron and Avni, 2004). In addition, recent studies have revealed that the prototypic MAMP flagellin can also induce HR in plant cells (Naito et al, 2008).…”
Section: Final Outcome Of the Response: Hr Or No Hr?mentioning
confidence: 98%